Phoxim induces neurotoxicity and intestinal damage in Caenorhabditis elegans - Zhang, Mengyuan; Zhao, Xin; Bai, Hua; Wang, Qi; Zou, Wei (Frontiers in Pharmacology, 2025)
IntroductionPhoxim (chemical name O-α-cyanophenylamino-O, O-diethyl phosphorothioate, molecular formula C12H15N2O3PS) is classified as a high-efficiency, low-toxicity organophosphorus insecticide. Its primary mechanism of action involves inhibition of cholinesterase activity in insects, which disrupts nerve conduction, ultimately leading to paralysis and death.MethodsThe effects of phoxim exposure (0.5, 1, and 2.5 µg/mL) on survival, neurological function, and intestinal integrity in Caenorhabditis elegans (C.elegans) were investigated.ResultsPhoxim at all concentrations significantly increased the mortality rate of C. elegans. Fluorescence microscopy revealed that 2.5 µg/mL phoxim reduced dopaminergic neural processes in the BZ555 transgenic strain of C. elegans from 4 to 2, and 0.5 and 1 µg/mL phoxim accelerated amyloid beta (Aβ)-induced paralysis in the CL4176 strain, with complete paralysis observed at 32 and 36 h, respectively. FD&C Blue #1 staining demonstrated intestinal damage in 46.7% and 68.3% of C. elegans exposed to phoxim at 1 and 2.5 µg/mL, respectively. Exposure to 1 µg/mL phoxim decreased enterocyte numbers and reduced autophagic vesicles in the lgg-1::GFP strain of C. elegans from 1.8 to 1.3. qPCR analysis revealed downregulation of autophagy-related genes (vps-34, atg-13, and unc-51) by 0.53-, 0.43-, and 0.36-fold of the control levels, respectively. RNAi targeting the eat-2 gene further confirmed the impact of phoxim on cell survival through the autophagy pathway.DiscussionOur results indicate that phoxim exposure reduces dopaminergic neuron integrity, accelerates Aβ-induced paralysis, and damages intestinal cells through inhibition of autophagy in C. elegans.